2023
DOI: 10.21896/jksmch.2023.27.1.24
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Perinatal Outcomes of Natural Childbirth Led by Midwives: A Retrospective Study

Abstract: Purpose: The purpose of this study was to suggest the importance of natural childbirth by investigating the results of midwife-led perinatal periods and whether they were positive experiences for both individual women and their families.Methods: This retrospective study aimed to confirm the perinatal outcomes of midwife-attended vaginal births. Among 1,127 women who gave midwife-led birth in Gyeonggi-do, Seoul between January 1, 2019 and December 31, 2021, data were collected for 829 women. Records were exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…Another study examined the perinatal health outcomes for mothers who chose midwife-led natural childbirth at birthing centers. It found that these outcomes were superior to those of mothers who delivered in hospitals [ 11 ]. Specifically, mothers at birthing centers experienced lower risks of perineal tears, postpartum hemorrhage, and cesarean sections, along with fewer complications related to newborn Apgar scores and meconium staining.…”
Section: Performance Of the Nursing Workforce In The Field Of Women’s...mentioning
confidence: 99%
“…Another study examined the perinatal health outcomes for mothers who chose midwife-led natural childbirth at birthing centers. It found that these outcomes were superior to those of mothers who delivered in hospitals [ 11 ]. Specifically, mothers at birthing centers experienced lower risks of perineal tears, postpartum hemorrhage, and cesarean sections, along with fewer complications related to newborn Apgar scores and meconium staining.…”
Section: Performance Of the Nursing Workforce In The Field Of Women’s...mentioning
confidence: 99%
“…우리나라 도 산과의사 현실은 벼랑 끝이라고 한다 (Ko, 2023). 최근 소아 청소년과 의사회의 폐과선언까지 사실 일본보다 더 심각한 산 소아과 의료인력의 공백을 보여주고 있다 (Park, 2023).…”
unclassified
“…이제 우리나라도 병원 내 조산원 제도를 도입해야 할 시정에 왔다고 생각한다. 저위험 임산부를 병원 내에 조산원을 두어 병 원과 유사한 안전한 의료환경을 구비하여 조산사와 함께 자연 출산을 하고 모유수유 성공까지 할 수 있는 임산부가 만족하는 자연출산을 격려한다면 다음 출산을 계획하게 되어 저출산에서 도 탈피할 수 있는 장점까지 있게 될 것이다 (An et al, 2023). 또 한 개원조산사와 병원조산사의 전문직업성과 직무만족도 비교 연구 (Kim, 2017) (Lee & Kim, 2003;Song & Park, 2020) https://doi.org/10.21896/jksmch.2023.27.2.119 125…”
unclassified